Designing Online Marketplace To Resolve Marketing Problem For Small and Medium Enterprises (SMEs) - Aditya Hermawan; Aniek Murniati (University of Islam Malang, 2017)
The study aims to design an online marketplace to provide solutions to problems faced by Small and Medium Enterprises (SMEs), the difficulty to market their products online. One of the problems faced by SMEs is difficult to market their products online. One of the solutions that we provide is by designing an online marketplace to solve marketing problems effectively. We found that SMEs have attempted to market their products through social media such as facebook, twitter and others. In addition, some SMEs also have a website and advertise their products through online advertising. However, many of those who did not know how to market products online in order to increase sales. We designed an online marketplace for SMEs based on the concept of e-commerce to resolve the problems faced by SMEs, the effective marketing. The online market design is made taking into account the needs of SMEs as well as customer needs. Therefore, this study was conducted to SMEs in Malang, East Java, IndonesiaÂ and the people who often make purchases online.With the existence of the online market, SMEs can increase sales lead to increased profits for SMEs.Keyword: Online market, E-Commerce, Maketing